2008
DOI: 10.1002/jmor.10684
|View full text |Cite
|
Sign up to set email alerts
|

Cypris morphology in the barnacles Ibla and Paralepas (Crustacea: Cirripedia Thoracica) implications for cirripede evolution

Abstract: We used scanning electron microscopy (SEM) to describe cypris morphology in species of the barnacles Ibla and Paralepas, both of which are pivotal in understanding cirripede evolution. In Ibla, we also studied late naupliar stages with video and SEM. Special emphasis was put on the lattice organs, the antennules and the thorax and telson. In Paralepas we had settled specimens only and could therefore only investigate the carapace with the lattice organs. Cyprids of Ibla quadrivalvis and Paralepas dannevigi hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The attachment disc is encircled by a velum in C. mitella and I. quadrivalvis and by a s kirt in O. angulata . In C. mitella a series of slender cuticular flaps forms the distinct velum, whereas the velum of I. quadrivalvis certainly does consist of small cuticular flaps (Hoeg et al , 2009). And the flaps in I. quadrivalvis do not run far down the side of the segment, therefore they differ from the long, narrow flaps in C. mitella and balanomorphans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The attachment disc is encircled by a velum in C. mitella and I. quadrivalvis and by a s kirt in O. angulata . In C. mitella a series of slender cuticular flaps forms the distinct velum, whereas the velum of I. quadrivalvis certainly does consist of small cuticular flaps (Hoeg et al , 2009). And the flaps in I. quadrivalvis do not run far down the side of the segment, therefore they differ from the long, narrow flaps in C. mitella and balanomorphans.…”
Section: Discussionmentioning
confidence: 99%
“…Within the Cirripedia, only the Acrothoracica have a separate abdomen, Rhizocephalan and thoracian cyprids have no free abdomen, and the cleaved telson (or abdomen–telson) connects directly with the thorax (Kolbasov et al , 1999; Høeg et al , 2009). Although there is no trace of an independent, abdominal body part in cyprids of I. quadrivalvis (Høeg et al , 2009), cypris larvae of the family Poecilasmatidae have a rudimentary abdomen which seems to consist of two small segments (Kolbasov et al , 2013). Cyprids of C. mitella also have a rudimentary abdomen according to our observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the cyprid larval morphotype (with an elongated head shield, six swimming thoracopods, and robust modified antennules) is considered a synapomorphy of Thecostraca (Høeg et al, 2004). R. reduncus differs from cirripede cyprids as it lacks attachment discs, and its abdomen extends past the head shield; a differentiated abdomen is a condition of Ascothoracida (Briggs et al, 2005;Høeg et al, 2009a). Based on the presence of five shell plates in a juvenile specimen, Høeg et al (2009b) suggested that R. reduncus may be placed on the cirripede stem lineage.…”
Section: Phylogenetic Justificationmentioning
confidence: 99%
“…Lastly, it has been shown that precursors of the LOs of cyprids (or cyprid-like larvae) exist in nauplii in the form of pore-bearing setae (Walossek, Høeg & Shirley, 1996;Rybakov et al, 2003;Høeg et al, 2009). …”
Section: The Other Dorsal Sensory Pit Organsmentioning
confidence: 99%